A Companion to Benjamin Franklin - Waldstreicher, David (Hoboken : John Wiley & Sons, 2011)
This companion provides a comprehensive survey of the life, work and legacy of Benjamin Franklin - the oldest, most distinctive, and multifaceted of the founders. Includes contributions from across a range of academic disciplines Combines traditional and cutting-edge scholarship, from accomplished and emerging experts in the field Pays special attention to the American Revolution, the Enlightenment, journalism, colonial American society, and themes of race, class, and gender Places Franklin in the context of recent work in political theory, American Studies, American literature, material cultur.
Print version record.
Keywords: Franklin, Benjamin, -- 1706-1790.; Franklin, Benjamin, -- 1706-1790.; 1600-1799; Statesmen -- United States -- Biography; Scientists -- United States -- Biography; Inventors -- United States -- Biography; Printers -- United States -- Biography; Franklin, Benjamin -- 1706-1790.; Inventors -- United States -- Biography; Printers -- United States -- Biography; Scientists -- United States -- Biography; Statesmen -- United States -- Biography; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- Intellectual life -- 18th century; HISTORY -- United States -- Colonial Period (1600-1775); HISTORY -- United States -- State & Local -- General; Intellectual life; Inventors; Printers; Scientists; Statesmen; United States -- Intellectual life -- 18th century; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States; Electronic books; Biography; History